C²+14 is the expression of sum of C squared and 14
An expression is combination of variables, numbers and operators.
Given sentence is sum of C squared and 14
Sum is nothing but the operation of addition o simply it is addition.
Squared means a number is multiplied to itself.
sum of C squared and 14 means C is multiplied to itself and added with forteen
C²+14
The sum of C squared and 14 is C²+14
Hence, C²+14 is the expression of sum of C squared and 14
To learn more on Expressions click:
#SPJ3
Answer:
C^2 + 14
Step-by-step explanation:
Answer:
, , and
Step-by-step explanation:
1.
Let's find a common denominator:
=
2/(x-1)x(x+1)
2.
Distribute exponents:
2^3(y^2)^3
__________
8^2(y)^2
Numerator:
2 to the power of 3 equals (2 · 2 · 2) = 8
y to the power of 2 to the power of 3 equals, y to the power of 6 (this is because when exponents in parenthesis are held to the power of another number outside of the parenthesis, you multiply them)
Now let's simplify the denominator:
8 to the power of 2 equals (8 · 8) = 64
y to the power of 2 is just y to the power of 2, so our new expression is:
Let's cancel the terms further:
8/64 can be simplified to 1/8
And when you cancel exponents, you subtract the denominator's exponent from the numerator's exponent ( = )
Now put them together:
Which is,
=
y^4/8
3.
The common denominator for both fractions is 3t, so let's make -1/3's denominator 3t by multiplying t to both the numerator and the denominator:
-1 · t
_____ = -1(t)/3t = -t/3t
3 · t
Now let's solve for the numerator:
(t + 2) - t, the t's cancel out, t - t + 2 = 2
And the denominator stays the same, so it will still equal 3t
Finally, you'll get an answer of
=
2/3^2
Answer:
Step-by-step explanation:
S = 2WL + 2LH + 2WH
S - 2WH = 2WL + 2LH
S - 2WH = L(2W + 2H)
(S - 2WH) / (2W + 2H) = L <===